2018
DOI: 10.1080/15384101.2018.1442622
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Crabtree/Warburg effect in a dynamic perspective: a fitness advantage against sugar-induced cell death

Abstract: The mechanisms behind the Warburg effect in mammalian cells, as well as for the similar Crabtree effect in the yeast Saccharomyces cerevisiae, are still a matter of debate: why do cells shift from the energy-efficient respiration to the energy-inefficient fermentation at high sugar concentration?This review reports on the strong similarities of these phenomena in both cell types, discusses the current ideas, and provides a novel interpretation of their common functional mechanism in a dynamic perspective. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 131 publications
(149 reference statements)
2
45
0
Order By: Relevance
“…On the one hand, high glycolytic flux will favor fermentation and production of building blocks; on the other hand, it will reduce respiration capabilities. Hence, it is observed that ATP is produced by respiration at low glucose uptake rate [ 52 , 53 ], which is consistent with our observations (this study) and [ 12 ]. It turn, high glucose uptake rate and high glycolytic flux will correspond to higher biosynthetic rate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the one hand, high glycolytic flux will favor fermentation and production of building blocks; on the other hand, it will reduce respiration capabilities. Hence, it is observed that ATP is produced by respiration at low glucose uptake rate [ 52 , 53 ], which is consistent with our observations (this study) and [ 12 ]. It turn, high glucose uptake rate and high glycolytic flux will correspond to higher biosynthetic rate.…”
Section: Discussionsupporting
confidence: 92%
“…The role of fructose 1,6-bisphosphate (F1,6bP) as a regulator of respiratory activity is well known. F1,6bP directly inhibits the activity of complex II and III of the respiratory chain, but its level also correlates with the glucose uptake rate, and high F1,6bP content indicates high glycolytic flux [ 34 , 53 , 55 ]. It is worth underlining that a lower concentration of F1,6bP is observed in the Δ hxk2 strain cells [ 38 , 55 ], although as shown by the latest research, induction of the Crabtree effect and regulation of respiration also depend on the concentration of glucose-6-phosphate (G6P), which is regarded as a stimulator of the respiratory chain [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, human cancer cells typically grow by aerobic glycolysis, known as the Warburg effect (Warburg, ), thought to increase biosynthetic capacity (Diaz‐Ruiz et al , ; Lunt & Vander Heiden, ; Costa & Frezza, ). Proposed explanations for how aerobic glycolysis allows faster proliferation involve efficient resource allocation (Basan et al , ; Mori et al , ), molecular crowding (Andersen & von Meyenburg, ; Zhuang et al , ; Vazquez & Oltvai, ; Szenk et al , ), an upper limit to the cellular Gibbs energy dissipation rate (Niebel et al , ), among others (Dai et al , ; de Alteriis et al , ; de Groot et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, human cancer cells typically grow by aerobic glycolysis, known as the Warburg effect 10 , thought to increase biosynthetic capacity [11][12][13] . Proposed explanations for how aerobic glycolysis allows faster proliferation involve efficient resource allocation 14,15 and molecular crowding [16][17][18][19] , among others [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%